Особенности весеннего развития яиц непарного шелкопряда как фактор экологической пластичности его популяции в условиях Нижнего Приднепровья - Деревянко, Н.М. (Вестник зоологии, 1980)
Each food race (micropopulation) of the gypsy moth in the Lower Dnieper area is characterized by its own genotype of individua/s. The intensity ot protein metabolism in eggs of the postdiapause development in these individuals is affected by a sum of effective temperatures providing both the completeness of the development and birth of caterpillars by the moment of leafing of the preferable food speices and the beginning of the latter vegetation.